Echolalia in patients with primary progressive aphasia. (23rd December 2020) - Ota, Shoko; Kanno, Shigenori; Morita, Ayumi; Narita, Wataru; Kawakami, Nobuko; Kakinuma, Kazuo; Saito, Yumiko; Kobayashi, Erena; Baba, Toru; Iizuka, Osamu; Nishio, Yoshiyuki; Matsuda, Minoru; et al.
Abstract: Objective: This study aimed to examine echolalia and its related symptoms and brain lesions in primary progressive aphasia (PPA). Methods: Forty‐five patients with PPA were included: 19 nonfluent/agrammatic variant PPA (nfvPPA), 5 semantic variant PPA, 7 logopenic variant PPA, and 14 unclassified PPA patients. We detected echolalia in unstructured conversations. An evaluation of language function and the presence of parkinsonism, grasp reflex, imitation behaviour, and disinhibition were assessed. We also measured regional cerebral blood flow (rCBF) using single‐photon emission computed tomography. Results: Echolalia was observed in 12 nfvPPA and 2 unclassified PPA patients. All patients showed mitigated echolalia. We compared nfvPPA patients with echolalia (echolalia group) to those without echolalia (non‐echolalia group). The median age of the echolalia group was significantly lower than that of the non‐echolalia group, and the echolalia group showed a significantly worse auditory comprehension performance than the non‐echolalia group. In contrast, the performance of repetition tasks was not different between the two groups. The prevalence of imitation behaviour in the echolalia group was significantly higher than that in the non‐echolalia group. The rCBFs in the bilateral pre‐supplementary motor area and bilateral middle cingulate cortex in the echolalia group were significantly lower than those in the non‐echolalia group. Conclusions: These findings suggest that echolalia is characteristic of nfvPPA patients with impaired comprehension. Reduced inhibition of the medial frontal cortex with release activity of the anterior perisylvian area account for the emergence of echolalia. Abstract : Echolalia is characteristic of nonfluent/agrammatic variant primary progressive aphasia (nfvPPA). Echolalia in patients with nfvPPA is provoked by compensation for poor auditory comprehension and inadequate inhibitory control related to dysfunction in the pre‐supplementary motor area and middle cingulate cortex.